Application of CBT to Improve Self Esteem And Learning Motivation of Fostered Children (Case Study of Special Development Institution for Children Class I Tangerang) - Nailusyarifa, Andin Noviar; Equatora, Muhammad Ali; Hamzah, Imaddudin; Tando, Cahyoko Edi (Innovative: Journal Of Social Science Research, 2024)
Children's learning motivation has a significant influence on adolescent behavior, which can lead to delinquency and legal issues, ultimately resulting in them becoming residents of LPKA. Several studies have shown that children undergoing rehabilitation at LPKA experience various psychological impacts, one of which is a decrease in self-esteem, which is considered a person's perception of themselves. Cognitive Behavioral Therapy (CBT) is one of the therapeutic methods widely used to address issues of self-esteem and motivation. This study aims to evaluate the application of Cognitive Behavioral Therapy in enhancing the self-esteem and learning motivation of residents at LPKA Class I Tangerang. This research used an experimental qualitative method by providing CBT for six sessions to three residents, using the Rosenberg Self-Esteem Scale (RSES) and the Motivated Strategies for Learning Questionnaire (MSLQ) as measurement tools. The results of the study showed an increase in the average self-esteem and learning motivation of the residents before and after the CBT intervention.